2006
DOI: 10.1186/1471-2164-7-92
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes of human prostate cells

Abstract: Background: The gene expression profiles of most human tissues have been studied by determining the transcriptome of whole tissue homogenates. Due to the solid composition of tissues it is difficult to study the transcriptomes of individual cell types that compose a tissue. To overcome the problem of heterogeneity we have developed a method to isolate individual cell types from whole tissue that are a source of RNA suitable for transcriptome profiling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 30 publications
0
91
0
Order By: Relevance
“…The majority of group C genes were indeed overexpressed in patient-derived luminal compared to basal cells (Oudes et al., 2006) (Figure 4A and S3), implying that another transcription factor, distinct from RA, may regulate group C to sustain and promote gene expression during luminal differentiation. Because systemic and niche-driven AR-mediated signaling is the main regulator of luminal differentiation in prostate and is capable of inducing luminal differentiation, even in 3D culture, with an obligatory contribution from stroma (Lang et al., 2006), we assessed the responsiveness of group C to AR stimulation in publically available microarray data.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of group C genes were indeed overexpressed in patient-derived luminal compared to basal cells (Oudes et al., 2006) (Figure 4A and S3), implying that another transcription factor, distinct from RA, may regulate group C to sustain and promote gene expression during luminal differentiation. Because systemic and niche-driven AR-mediated signaling is the main regulator of luminal differentiation in prostate and is capable of inducing luminal differentiation, even in 3D culture, with an obligatory contribution from stroma (Lang et al., 2006), we assessed the responsiveness of group C to AR stimulation in publically available microarray data.…”
Section: Resultsmentioning
confidence: 99%
“…Differential gene expression analysis from array datasets was described in our previous publications [3, 44]. The obtained array CEL files were loaded into GeneSpring 7.2 (Agilent Technologies), which used an analysis algorithm of the open source Bioconductor project [45].…”
Section: Methodsmentioning
confidence: 99%
“…Small miRNA in vesicles are transported from producer cell to recipient cell to alter gene expression [2]. In benign prostate glands, three major cell types can be distinguished: CD26 + luminal secretory cells, CD104 + basal epithelial cells and CD49a + stromal cells [3]. In tumor glands only two major cell types are distinguished: CD26 + cancer epithelial cells and CD90 + cancer-associated stromal cells [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, immunoelectron microscopic analysis with autoantibodies that recognize several centromeric proteins revealed that each pre-kinetochore complex forms a stable, but highly dynamic association with the filaments of the nuclear matrix, proposing that the strikingly mobile properties of the centromeric complex may be facilitated by anchoring to the matrix network (39). Historically, alterations in the composition, number, size, and intranuclear localization of nucleoli were used as an early indication of cancer and to distinguish a few types of tumor cells from normal cells (40,41). Alterations in the nuclear matrix composition are also known to be cell type-and tumor-specific and have been used for the development of protein biomarkers of cancer (42).…”
Section: Discussionmentioning
confidence: 99%